Glass fiber impregnating compound and preparation method thereof
By using a specific composition of glass fiber wetting agent, the problem of poor film formation uniformity on the surface of long glass fibers is solved, and the mechanical properties and aging resistance of composite materials are improved.
Patent Information
- Application Number
- CN202411745497.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-21
AI Technical Summary
The existing glass fiber wetting agents have poor film formation uniformity on the surface of long glass fibers, which affects the appearance quality and mechanical properties of composite materials.
A glass fiber wetting agent composed of coupling agent, lubricant, film forming agent A, film forming agent B, film forming auxiliary agent, interface dispersant and wetting agent is used to ensure that the film forming agent spreads evenly on the surface of the long glass fiber through specific formula ratios and preparation methods.
The uniformity of the surface wetting film of long glass fiber is significantly improved, the corrosion resistance, wear resistance and high temperature resistance of composite materials are enhanced, and the film formation rate and mechanical properties are improved.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of glass fiber surface treatment, and particularly relates to a glass fiber sizing agent and a preparation method thereof. Background Art
[0002] Polyphenylene sulfide, referred to as PPS, is a kind of thermoplastic resin and has broad application prospects in the fields of automobiles, electronics, chemicals and papermaking. In order to further improve the strength, heat resistance and dimensional stability of polyphenylene sulfide and reduce the cost of PPS, it is generally necessary to add a certain amount of reinforcing fiber to make a fiber-reinforced PPS composite material; for example, long glass fiber is added to make a long glass fiber reinforced PPS composite material, and this preparation process is the LFT process; the length of the long glass fiber is generally greater than 5mm, and is currently commonly 6~25mm. Compared with traditional short fibers, the introduction of long fibers enables the prepared composite material to better transmit and disperse mechanical stress and thermal stress, thereby obtaining higher impact strength, tensile strength and bending strength, as well as better fatigue resistance, high temperature resistance, wear resistance, corrosion resistance and aging resistance.
[0003] In addition, since long glass fibers are generally composed of regularly arranged silicon-oxygen tetrahedrons at the microscopic level, during the fiber processing, due to the reconstruction of silicon-oxygen atoms, some oxygen atoms in the silicon-oxygen tetrahedrons are not completely combined with silicon atoms, thereby forming silanol (Si-OH); polyphenylene sulfide is a chain polymer composed of benzene rings and sulfur atoms connected alternately, lacking polar functional groups, which leads to poor interfacial compatibility between polyphenylene sulfide and long glass fibers, making it difficult to combine tightly, so it is necessary to use a wetting agent to form a polymer film on the surface of the long glass fibers to enhance interfacial compatibility. And because the long glass fibers are long, uneven film thickness and distribution are prone to occur during impregnation, which will affect the appearance quality and mechanical properties of the parts of the long glass fibers that are not fully impregnated; for example, uneven impregnation films may lead to inconsistent bonding between long glass fiber filaments, making the glass fiber bundles easy to spread and poor bundling, and at the same time, the fibers are more likely to slide relative to each other, increasing friction resistance, thereby forming more hairiness on the fiber surface, which will also affect the tensile strength and other mechanical properties of the fiber-reinforced composites made later. Therefore, how to optimize the uniformity of film formation is one of the technical difficulties that the LFT process needs to solve.
[0004] Chinese patent CN115159866A discloses a glass fiber sizing agent suitable for PPS resin, which includes 1-5% water-based polyester polyurethane, 0.5-4% water-based polyimide, 0.2-1% water-based phenoxy resin emulsion, 0.5-1.2% lubricant, 0.5-1% coupling agent, and 0-0.1% antistatic agent. This patent has the following disadvantages: the drying rate of the water-based polyester polyurethane is slow, which affects the production efficiency on the one hand; on the other hand, especially for long glass fibers, the slow drying rate makes the sizing agent more susceptible to environmental changes during film formation, affecting the film uniformity, wear resistance, and impregnation of fibers and resins of the water-based polyester polyurethane.
[0005] Chinese patent CN104844018A discloses a glass fiber sizing agent, which includes 10-18% epoxy resin emulsion, 15-25% polyacrylate, 1-3% ammonia water, 0.2-0.8% white oil, 5-10% gasoline, 1-2% silane coupling agent and the balance of deionized water. This patent has the following disadvantages: the gasoline and ammonia water components in the sizing agent are highly volatile. When the glass fiber is actually processed, it needs to be stirred and soaked for a period of time at a certain temperature. At this time, the volatilization of gasoline and ammonia water will cause the concentration of epoxy resin emulsion and polyacrylate to gradually increase, increase the viscosity of the sizing agent, and deteriorate the fluidity. Especially for long glass fibers, it will affect the uniformity of the surface wetting film of the long glass fibers.
[0006] Therefore, how to solve the problem of poor uniformity of the film formed on the surface of the long glass fiber during the impregnation is one of the main research topics of those skilled in the art. Summary of the invention
[0007] The purpose of the present invention is to provide a glass fiber sizing to solve the problem of poor film uniformity when the glass fiber sizing is used to saturate long glass fibers. The present invention also provides a method for preparing the glass fiber sizing.
[0008] To achieve the above object, the technical solution adopted by the present invention is: The glass fiber sizing of the present invention is made of the following components, measured by mass percentage: 2-5wt% coupling agent, 0.05-1wt% lubricant, 2-10wt% film former A, 7-15wt% film former B, 0.1-0.7wt% film former, 0.5-5wt% interfacial dispersant, 0.5-6wt% wetting agent, and the rest is water; wherein the film former is polyaspartic acid ester.
[0009] in: The coupling agent is one or more of vinyl triethoxysilane, γ-(methacryloyloxy)propyl trimethoxysilane, γ-aminopropyl triethoxysilane, N-(β-aminoethyl)-γ-aminopropyl methyl dimethoxysilane or γ-glycidyl ether oxygen propyl trimethoxysilane.
[0010] The lubricant is one or more of glyceryl monostearate, glyceryl distearate, glyceryl tristearate, stearic acid amide, oleic acid amide or acetyl stearic acid amide.
[0011] The film-forming agent A is a phenolic epoxy resin emulsion.
[0012] The film-forming agent B is a polyester polyurethane emulsion or a polyether polyurethane emulsion.
[0013] The interfacial dispersant is sulfonated fatty alcohol polyoxyethylene ether or sulfonated fatty amine polyoxyethylene ether.
[0014] The wetting agent is polyether modified silicone emulsion.
[0015] The method for preparing the glass fiber sizing agent of the present invention comprises the following steps: (1) stirring and hydrolyzing the coupling agent with water to obtain a hydrolyzate; (2) diluting the lubricant with water and stirring to obtain a lubricant dilution solution; (3) diluting film-forming agent A and film-forming agent B with water and stirring to prepare a film-forming agent dilution solution; (4) adding the film-forming agent diluent, the film-forming aid and the hydrolyzate to the lubricant diluent in sequence and mixing them to obtain a blended liquid; (5) diluting the interfacial dispersant with water and stirring to obtain an interfacial dispersant dilution solution; (6) diluting the wetting agent with water and stirring to obtain a wetting agent dilution solution; (7) Add the interfacial dispersant dilution solution and the wetting agent dilution solution into the blended liquid and mix well, then add the remaining water and stir to obtain the glass fiber wetting agent.
[0016] In the step (1), the mass ratio of the coupling agent to water is 1:(3-10), and the hydrolysis time is 30-60 min; in the step (2), the mass ratio of the lubricant to water is 1:(1-20); in the step (3), the mass ratio of the total mass of the film-forming agent A and the film-forming agent B to water is 1:(1-3); in the step (5), the mass ratio of the interfacial dispersant to water is 1:(1-10); in the step (6), the mass ratio of the wetting agent to water is 1:(1-10).
[0017] In the step (2), the stirring temperature is 50-90° C.; in the step (7), the stirring time is 30-60 min.
[0018] The lubricant is selected from stearic acid glyceryl esters or amide compounds, which play the role of internal lubrication; on the one hand, it can penetrate into the tiny gaps between the aggregated polymer molecular chains to form a lipid bilayer, thereby effectively reducing the adhesion between the polymer molecular chains and ensuring the dispersion and fluidity of the polymer molecular chains; on the other hand, it can be distributed between the long glass fiber and the processing surface of the processing equipment, reducing friction, improving the wear resistance of the long glass fiber, and reducing the amount of fluff.
[0019] The coupling agent is a silane coupling agent; on the one hand, it can improve the formability of the long glass fiber during the drawing process, and on the other hand, it can improve the mechanical properties of the long glass fiber reinforced PPS composite material; the siloxane group (-Si-O-) at one end of the silane coupling agent can undergo a condensation reaction with the silanol group (Si-OH) on the surface of the long glass fiber, and the active group (such as amino group, glycidyl ether group, etc.) at the other end can undergo a ring-opening reaction with the epoxy group in the phenolic epoxy resin, so that the film-forming agent A is tightly attached to the surface of the long glass fiber.
[0020] Film former A is phenolic epoxy resin emulsion, and film former B is polyester polyurethane emulsion or polyether polyurethane emulsion. Film former A and film former B are organic liquid phases with strong fluidity. They are entangled with PPS molecular chains through hydrogen bonding to form a complex network structure. When used in conjunction with a coupling agent, the interfacial compatibility between long glass fiber and PPS is effectively improved.
[0021] The interfacial dispersant is selected from sulfonated fatty alcohol polyoxyethylene ether or sulfonated fatty amine polyoxyethylene ether, and the interfacial dispersant belongs to anionic or nonionic surfactants; the interfacial dispersant can ensure the stability of the physical and chemical properties of the sizing agent, while not affecting the mechanical properties of the glass fiber reinforced composite material, and the interfacial dispersant can ensure the coating efficiency of the film former A and the film former B on the surface of the long glass fiber. The wetting agent is selected from polyether modified siloxane emulsion; it can reduce the surface tension of the long glass fiber, improve the adhesion of the film former A and the film former B, and reduce the migration and precipitation of the glass fiber sizing agent during the subsequent drying of the sizing film. In the present invention, it can be ensured that the film former has good compatibility with other components of the sizing agent and the stability of the prepared emulsion is guaranteed.
[0022] Most silane coupling agents are insoluble in water and tend to aggregate when existing alone, which reduces the contact area with the glass fiber. Therefore, the silane coupling agent undergoes a reversible hydrolysis reaction with water, which promotes the dispersibility of the silane coupling agent in water and the wettability with the long glass fiber.
[0023] The beneficial effects of the present invention are as follows: (1) The film-forming aid of the present invention is polyaspartic acid ester, which contains carbamate groups in the molecules of film-forming agent B, and is similar and compatible in chemical structure. Hydrogen bonds can be formed between polyaspartic acid ester and film-forming agent B molecules, and the molecular chains are entangled with each other, which improves the compatibility with film-forming agent B; the amino group or hydroxyl group in polyaspartic acid ester can react with the epoxy group in film-forming agent A, which improves its compatibility with film-forming agent A. In addition, polyaspartic acid ester is a new type of hindered amine, which reacts with the isocyanate group of film-forming agent B to form polyurea after curing. The formed impregnation film has excellent yellowing resistance, wear resistance and good toughness, and significantly improves the heat resistance, moisture resistance and hydrolysis resistance of the final long glass fiber reinforced PPS composite material. When the impregnation film is formed, the film formation rate is also faster.
[0024] (2) Polyaspartic acid ester is selected as the film-forming agent; under the spreading action of the interfacial dispersant and wetting agent, the film-forming agent A and the film-forming agent B are spread more evenly and densely on the surface of the long glass fiber, further improving the corrosion resistance, wear resistance and high temperature resistance. In addition, due to the good flexibility of the polyaspartic acid ester molecular chain, it is beneficial to reduce the rigidity of the film-forming agent A and the film-forming agent B, making the film-forming agent A and the film-forming agent B more likely to flow and rearrange under the action of thermal stress. Polyaspartic acid ester also makes it easier for the film-forming agent A and the film-forming agent B to be arranged into a tight and orderly impregnation film structure. This means that under the same conditions, after adding the film-forming agent, it is easier to reach the temperature required for film formation, reducing the phenomenon of performance damage such as increased fluff and decreased bundling of glass fibers caused by high temperature and high stress treatment. DETAILED DESCRIPTION
[0025] The present invention is specifically described and illustrated below in conjunction with embodiments.
[0026] Prepare the following raw materials: Film former A: phenolic epoxy resin emulsion, brand BS-2155F, produced by Bath Synthetic New Materials Company; Film former B: polyester polyurethane emulsion, brand PU-1810 / 1, produced by Covestro Polymers (China) Co., Ltd.; polyether polyurethane emulsion, brand PU 406, produced by Covestro Polymers (China) Co., Ltd.; Interfacial dispersant: sulfonated fatty alcohol polyoxyethylene ether, brand name AEO-9, produced by Jinan Ruilin Chemical; sulfonated fatty amine polyoxyethylene ether, brand name AC-1802, produced by Hangzhou Maochang Chemical; Wetting agent: polyether modified silicone emulsion, brand SF-8427, produced by Dow Corning.
[0027] Example 1 Prepare the raw materials according to the following mass parts and types: 2 parts of coupling agent, γ-(methacryloyloxy)propyltrimethoxysilane; 0.05 parts of lubricant, glyceryl monostearate; 3 parts of film-forming agent A, phenolic epoxy resin emulsion; 10 parts of film-forming agent B, polyester polyurethane emulsion; 0.1 parts of film-forming aid, polyaspartic acid ester; 4 parts of interfacial dispersant, sulfonated fatty alcohol polyoxyethylene ether; 6 parts of wetting agent, polyether modified siloxane emulsion; 74.85 parts of deionized water.
[0028] Preparation of glass fiber sizing agent: adding coupling agent to 20 parts of deionized water, stirring and hydrolyzing at room temperature for 45 minutes to obtain hydrolyzate; At 65°C, the lubricant is added to 1 part of deionized water and stirred evenly, and then cooled to room temperature to obtain a lubricant dilution solution; at room temperature, the film former A and the film former B are added to 26 parts of deionized water and stirred evenly to obtain a film former dilution solution; the film former dilution solution, the film forming aid and the hydrolyzate are sequentially added to the lubricant dilution solution and mixed evenly to obtain a blend solution; The wetting agent was added into 12 parts of deionized water at room temperature and stirred evenly to obtain a wetting agent dilution solution; the interfacial dispersant was added into 8 parts of deionized water and stirred evenly to obtain an interfacial dispersant dilution solution; the wetting agent dilution solution and the interfacial dispersant dilution solution were added into the blended solution, the remaining deionized water was added into the blended solution, and the mixture was stirred for 30 minutes to obtain a glass fiber wetting agent.
[0029] Example 2 Prepare the raw materials according to the following mass parts and types: 3 parts of coupling agent, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane; 0.5 parts of lubricant, oleic acid amide; 10 parts of film-forming agent A, phenolic epoxy resin emulsion; 7 parts of film-forming agent B, polyester polyurethane emulsion; 0.5 parts of film-forming aid, polyaspartic acid ester; 4 parts of interfacial dispersant, sulfonated fatty alcohol polyoxyethylene ether; 0.5 parts of wetting agent, polyether modified siloxane emulsion; 74.5 parts of deionized water.
[0030] Preparation of glass fiber sizing agent: adding coupling agent to 15 parts of deionized water, stirring and hydrolyzing at room temperature for 30 minutes to obtain hydrolyzate; At 90°C, the lubricant was added to 1 part of deionized water and stirred evenly, and then cooled to room temperature to obtain a lubricant dilution solution; at room temperature, the film former A and the film former B were added to 17 parts of deionized water and stirred evenly to obtain a film former dilution solution; the film former dilution solution, the film forming aid and the hydrolyzate were sequentially added to the lubricant dilution solution and mixed evenly to obtain a blend solution; The wetting agent was added into 5 parts of deionized water at room temperature and stirred evenly to obtain a wetting agent dilution solution; the interfacial dispersant was added into 10 parts of deionized water and stirred evenly to obtain an interfacial dispersant dilution solution; the wetting agent dilution solution and the interfacial dispersant dilution solution were added into the blended solution, the remaining deionized water was added into the blended solution, and the mixture was stirred for 40 minutes to obtain a glass fiber wetting agent.
[0031] Example 3 Prepare the raw materials according to the following mass parts and types: 3 parts of coupling agent, γ-glycidyloxypropyltrimethoxysilane; 1 part of lubricant, stearic acid amide; 2 parts of film-forming agent A, phenolic epoxy resin emulsion; 10 parts of film-forming agent B, polyester polyurethane emulsion; 0.7 parts of film-forming aid, polyaspartic acid ester; 5 parts of interfacial dispersant, sulfonated fatty alcohol polyoxyethylene ether; 1 part of wetting agent, polyether modified silicone emulsion; 77.3 parts of deionized water.
[0032] Preparation of glass fiber sizing agent: adding coupling agent to 15 parts of deionized water, stirring and hydrolyzing at room temperature for 60 minutes to obtain a hydrolyzate; At 80°C, the lubricant was added to 1 part of deionized water and stirred evenly, and then cooled to room temperature to obtain a lubricant dilution solution; at room temperature, the film former A and the film former B were added to 36 parts of deionized water and stirred evenly to obtain a film former dilution solution; the film former dilution solution, the film forming aid and the hydrolyzate were sequentially added to the lubricant dilution solution and mixed evenly to obtain a blend solution; The wetting agent was added into 10 parts of deionized water at room temperature and stirred evenly to obtain a wetting agent dilution solution; the interfacial dispersant was added into 5 parts of deionized water and stirred evenly to obtain an interfacial dispersant dilution solution; the wetting agent dilution solution and the interfacial dispersant dilution solution were added into the blended solution, the remaining deionized water was added into the blended solution, and the mixture was stirred for 35 minutes to obtain a glass fiber wetting agent.
[0033] Example 4 Prepare the raw materials according to the following mass parts and types: 5 parts of coupling agent, vinyl triethoxy silane; 0.05 parts of lubricant, acetyl stearamide; 8 parts of film-forming agent A, phenolic epoxy resin emulsion; 7 parts of film-forming agent B, polyether polyurethane emulsion; 0.1 parts of film-forming aid, polyaspartic acid ester; 5 parts of interfacial dispersant, sulfonated fatty amine polyoxyethylene ether; 3 parts of wetting agent, polyether modified siloxane emulsion; 71.85 parts of deionized water.
[0034] Preparation of glass fiber sizing agent: adding coupling agent to 20 parts of deionized water, stirring and hydrolyzing at room temperature for 50 minutes to obtain hydrolyzate; At 50°C, the lubricant is added to 1 part of deionized water and stirred evenly, and then cooled to room temperature to obtain a lubricant dilution solution; at room temperature, the film former A and the film former B are added to 30 parts of deionized water and stirred evenly to obtain a film former dilution solution; the film former dilution solution, the film forming aid and the hydrolyzate are sequentially added to the lubricant dilution solution and mixed evenly to obtain a blended solution; The wetting agent was added into 3 parts of deionized water at room temperature and stirred evenly to obtain a wetting agent dilution solution; the interfacial dispersant was added into 10 parts of deionized water and stirred evenly to obtain an interfacial dispersant dilution solution; the wetting agent dilution solution and the interfacial dispersant dilution solution were added into the blended solution, the remaining deionized water was added into the blended solution, and the mixture was stirred for 50 minutes to obtain a glass fiber wetting agent.
[0035] Example 5 Prepare the raw materials according to the following mass parts and types: 5 parts of coupling agent, γ-aminopropyltriethoxysilane; 0.2 parts of lubricant, glyceryl monostearate; 10 parts of film-forming agent A, phenolic epoxy resin emulsion; 10 parts of film-forming agent B, polyether polyurethane emulsion; 0.3 parts of film-forming aid, polyaspartic acid ester; 0.5 parts of interfacial dispersant, sulfonated fatty alcohol polyoxyethylene ether; 5 parts of wetting agent, polyether modified siloxane emulsion; 69 parts of deionized water.
[0036] Preparation of glass fiber sizing agent: adding coupling agent to 15 parts of deionized water, stirring and hydrolyzing at room temperature for 55 minutes to obtain hydrolyzate; At 70°C, the lubricant is added to 1 part of deionized water and stirred evenly, and then cooled to room temperature to obtain a lubricant dilution solution; at room temperature, the film former A and the film former B are added to 40 parts of deionized water and stirred evenly to obtain a film former dilution solution; the film former dilution solution, the film forming aid and the hydrolyzate are sequentially added to the lubricant dilution solution and mixed evenly to obtain a blended solution; The wetting agent was added into 5 parts of deionized water at room temperature and stirred evenly to obtain a wetting agent dilution solution; the interfacial dispersant was added into 5 parts of deionized water and stirred evenly to obtain an interfacial dispersant dilution solution; the wetting agent dilution solution and the interfacial dispersant dilution solution were added into the blended solution, the remaining deionized water was added into the blended solution, and the mixture was stirred for 45 minutes to obtain a glass fiber wetting agent.
[0037] Example 6 Prepare the raw materials according to the following mass parts and types: 5 parts of coupling agent, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane; 0.5 parts of lubricant, glyceryl distearate; 2 parts of film-forming agent A, phenolic epoxy resin emulsion; 13 parts of film-forming agent B, polyether polyurethane emulsion; 0.5 parts of film-forming aid, polyaspartic acid ester; 1 part of interfacial dispersant, sulfonated fatty alcohol polyoxyethylene ether; 6 parts of wetting agent, polyether modified siloxane emulsion; 72 parts of deionized water.
[0038] Preparation of glass fiber sizing agent: adding coupling agent to 20 parts of deionized water, stirring and hydrolyzing at room temperature for 45 minutes to obtain hydrolyzate; At 60°C, the lubricant is added to 1 part of deionized water and stirred evenly, and then cooled to room temperature to obtain a lubricant dilution solution; at room temperature, the film former A and the film former B are added to 40 parts of deionized water and stirred evenly to obtain a film former dilution solution; the film former dilution solution, the film forming aid and the hydrolyzate are sequentially added to the lubricant dilution solution and mixed evenly to obtain a blend solution; The wetting agent was added into 6 parts of deionized water at room temperature and stirred evenly to obtain a wetting agent dilution solution; the interfacial dispersant was added into 1 part of deionized water and stirred evenly to obtain an interfacial dispersant dilution solution; the wetting agent dilution solution and the interfacial dispersant dilution solution were added into the blended solution, the remaining deionized water was added into the blended solution, and the mixture was stirred for 60 minutes to obtain a glass fiber wetting agent.
[0039] Example 7 Prepare the raw materials according to the following mass parts and types: 5 parts of coupling agent, γ-glycidyloxypropyltrimethoxysilane; 1 part of lubricant, glyceryl tristearate; 3 parts of film-forming agent A, phenolic epoxy resin emulsion; 15 parts of film-forming agent B, polyether polyurethane emulsion; 0.7 parts of film-forming aid, polyaspartic acid ester; 2 parts of interfacial dispersant, sulfonated fatty amine polyoxyethylene ether; 0.5 parts of wetting agent, polyether modified silicone emulsion; 72.8 parts of deionized water.
[0040] Preparation of glass fiber sizing agent: adding coupling agent to 20 parts of deionized water, stirring and hydrolyzing at room temperature for 45 minutes to obtain hydrolyzate; At 60°C, the lubricant was added to 1 part of deionized water and stirred evenly, and then cooled to room temperature to obtain a lubricant dilution solution; at room temperature, the film former A and the film former B were added to 32 parts of deionized water and stirred evenly to obtain a film former dilution solution; the film former dilution solution, the film forming aid and the hydrolyzate were sequentially added to the lubricant dilution solution and mixed evenly to obtain a blend solution; The wetting agent was added into 5 parts of deionized water at room temperature and stirred evenly to obtain a wetting agent dilution solution; the interfacial dispersant was added into 6 parts of deionized water and stirred evenly to obtain an interfacial dispersant dilution solution; the wetting agent dilution solution and the interfacial dispersant dilution solution were added into the blended solution, the remaining deionized water was added into the blended solution, and the mixture was stirred for 55 minutes to obtain a glass fiber wetting agent.
[0041] Comparative Example 1 Deionized water was used to replace the film-forming agent A to prepare the glass fiber sizing. The remaining steps and raw materials used were the same as those in Example 1.
[0042] Comparative Example 2 Deionized water was used to replace the film-forming agent B to prepare the glass fiber sizing agent. The remaining steps and raw materials used were the same as those in Example 1.
[0043] Comparative Example 3 Deionized water was used to replace the film-forming aid to prepare the glass fiber sizing agent. The remaining steps and raw materials used were the same as those in Example 1.
[0044] Test Example 1 Coating long glass fibers with glass fiber sizing: The glass fiber precursor was passed through a coating machine, and the glass fiber sizing agents prepared in Examples 1-7 and Comparative Examples 1-3 were used to coat the glass fiber precursor, and continuous long glass fibers were obtained by wire drawing. The mass of the combustible (i.e., the portion of the sizing agent attached to the long glass fiber) was required to account for 0.4-0.6% of the total mass of the long glass fiber. The hairiness of the long glass fiber treated with the glass fiber sizing agent was measured, and the specific data is shown in Table 1.
[0045] Specific measurement method and standard: Take the coated long glass fiber, pass it through the tension rod on the conventional hair testing equipment, run it continuously for 10 minutes, collect the hair at the tension rod and weigh it to get the data, the hairiness level is divided into five levels: a lot, more, normal, less, very little, the corresponding data ranges are: >4g, 2-4g, 1-1.9g, 0.5-0.9g, <0.5g (the above data range indicates the total mass of the hair collected after the hair testing equipment runs continuously for 10 minutes).
[0046]
[0047] Test Example 2 Preparation of pellets and specimens: Using 10 groups (Examples 1-7 and Comparative Examples 1-3, a total of 10 groups) of coated long glass fibers and PPS resin obtained in Test Example 1 as raw materials, conventional LFT-G equipment was used to prepare pellets of long glass fiber reinforced PPS composite materials. Part of the pellets were taken to test their impregnation properties, and the specific data are shown in Table 2; then the pellets were injection molded to obtain specimens, and the long glass fiber content in the specimens was required to be 40wt%. The mechanical properties of the specimens were tested, and the specific data are shown in Table 2.
[0048] Specific measurement methods and standards: The impregnation mainly counts the area of the cross-section white core (the white core is the part that is not fully impregnated) of the long glass fiber reinforced PPS composite material obtained by conventional LFT-G equipment, and divides the area into four levels: poor, general, better, and good. The corresponding white core areas are: >50%, 20-50%, 5-19.9%, and <5%. According to GB / T 1447-2005, the initial tensile strength of the sample is tested; after 200 hours of pressure cooker test (Pressure Cooker Test, PCT), the PCT-200h tensile strength of the sample is measured according to GB / T 1447-2005; according to the measured initial tensile strength and PCT-200h tensile strength, the tensile strength retention rate is calculated. Tensile strength retention rate = (PCT-200h tensile strength / tensile initial performance) × 100%.
[0049]
[0050] According to the data in Table 2, it can be seen that the glass fiber sizing agent prepared in the present invention is beneficial to improving the mechanical properties (better initial tensile properties) and aging resistance (better tensile strength retention) of the long glass fiber reinforced PPS composite material.
Claims
1. A glass fiber sizing agent, characterized in that: The composition is made of the following components in percentage by mass: coupling agent 2-5wt%, lubricant 0.05-1wt%, film former A 2-10wt%, film former B 7-15wt%, film former 0.1-0.7wt%, interfacial dispersant 0.5-5wt%, wetting agent 0.5-6wt%, and the rest is water; The film-forming aid is polyaspartic acid ester.
2. The glass fiber sizing agent according to claim 1, characterized in that: The coupling agent is one or more of vinyl triethoxysilane, γ-(methacryloyloxy)propyl trimethoxysilane, γ-aminopropyl triethoxysilane, N-(β-aminoethyl)-γ-aminopropyl methyl dimethoxysilane or γ-glycidyloxypropyl trimethoxysilane.
3. The glass fiber sizing agent according to claim 1, characterized in that: The lubricant is one or more of glyceryl monostearate, glyceryl distearate, glyceryl tristearate, stearic acid amide, oleic acid amide or acetyl stearic acid amide.
4. The glass fiber sizing agent according to claim 1, characterized in that: Film former A is a phenolic epoxy resin emulsion.
5. The glass fiber sizing agent according to claim 1, characterized in that: The film-forming agent B is a polyester polyurethane emulsion or a polyether polyurethane emulsion.
6. The glass fiber sizing agent according to claim 1, characterized in that: The interfacial dispersant is sulfonated fatty alcohol polyoxyethylene ether or sulfonated fatty amine polyoxyethylene ether.
7. The glass fiber sizing agent according to claim 1, characterized in that: The wetting agent is polyether modified silicone emulsion.
8. A method for preparing the glass fiber sizing according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) stirring and hydrolyzing the coupling agent with water to obtain a hydrolyzate; (2) diluting the lubricant with water and stirring to obtain a lubricant dilution solution; (3) diluting film-forming agent A and film-forming agent B with water and stirring to prepare a film-forming agent dilution solution; (4) adding the film-forming agent diluent, the film-forming aid and the hydrolyzate to the lubricant diluent in sequence and mixing them to obtain a blended liquid; (5) diluting the interfacial dispersant with water and stirring to obtain an interfacial dispersant dilution solution; (6) diluting the wetting agent with water and stirring to obtain a wetting agent dilution solution; (7) Add the interfacial dispersant dilution solution and the wetting agent dilution solution into the blended liquid and mix well, then add the remaining water and stir to obtain the glass fiber wetting agent.
9. The method for preparing the glass fiber sizing according to claim 8, characterized in that: In step (1), the mass ratio of the coupling agent to water is 1:(3-10), and the hydrolysis time is 30-60 min; in step (2), the mass ratio of the lubricant to water is 1:(1-20); in step (3), the mass ratio of the total mass of the film-forming agent A and the film-forming agent B to water is 1:(1-3); in step (5), the mass ratio of the interfacial dispersant to water is 1:(1-10); in step (6), the mass ratio of the wetting agent to water is 1:(1-10).
10. The method for preparing the glass fiber sizing according to claim 8, characterized in that: In step (2), the stirring temperature is 50-90° C.; in step (7), the stirring time is 30-60 min.
Citation Information
Patent Citations
Glass fiber impregnating compound
CN104844018A
Glass fiber impregnating compound suitable for PPS resin and preparation method of glass fiber impregnating compound
CN115159866A
Cited By
High-adhesion glass fiber impregnating compound and preparation method thereof
CN122325131A